2019
DOI: 10.1038/s41586-019-1736-8
|View full text |Cite
|
Sign up to set email alerts
|

Voxelated soft matter via multimaterial multinozzle 3D printing

Abstract: is a co-founder of Voxel8, Inc. and Mark Skylar-Scott owns stock in Formlabs. A patent has been filed by Harvard University on this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
523
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 754 publications
(554 citation statements)
references
References 30 publications
0
523
0
1
Order By: Relevance
“…Last November, Lewis and her lab described a printer that can rapidly switch between different polymer inks or mix them as it prints a single object 12 . This means objects can be printed with both flexible and rigid parts.…”
Section: All Together Nowmentioning
confidence: 99%
“…Last November, Lewis and her lab described a printer that can rapidly switch between different polymer inks or mix them as it prints a single object 12 . This means objects can be printed with both flexible and rigid parts.…”
Section: All Together Nowmentioning
confidence: 99%
“…Strategically designed, well‐defined 3D architectures could offer great opportunities, that are unavailable in their 2D counterparts, for a broad spectrum of applications, such as microelectronics, bioelectronics, photonics and optoelectronics, micro‐electromechanical systems, metamaterials, energy storage and harvesting, soft robotics, and many others. [ 1–22 ] Existing manufacturing techniques of 3D structures mainly include 3D printing, templated growth, fluidic self‐assembly, and mechanically guided 3D assembly. [ 1–22 ] Among these methods, the mechanically guided 3D assembly has recently attracted broad attention in the scientific community.…”
Section: Figurementioning
confidence: 99%
“…Reproduced with permission. [6] Copyright 2019, Springer Nature. d) Direct fabrication of electrolyte from printable inks at an elevated temperature using solid poly(vinylidene fluoride-hexafluoropropylene) matrices and a Li + -conducting ionic-liquid electrolyte, which was modified by the addition of ceramic fillers to give an ionic conductivity of 0.78 × 10 −3 S cm −1 .…”
Section: Reproducibility and Mass Production In 3d Printed Eesdsmentioning
confidence: 99%
“…[5] However, it is exciting that Lewis et al have reported soft matter printing using multinozzle printing, thereby enabling massively parallel and complex multimaterial printing at the voxel level. [6] Scheme 1 summarizes some of the aims of AM in 3D printable batteries and supercapacitors, the materials, electrodes and printing innovation required to realize printable EESD technology.…”
Section: Introduction and Contextmentioning
confidence: 99%